Evaluating cytotoxicity potency of glucomoringin from the seeds of Moringa oleifera lam against prostate cancer cell line, PC-3 - Abdul Karim, Nurul Ashikin (2019)
Inhibition of several protein pathways involved in cancer cell regulation is a necessary key in the discovery of cancer chemotherapy. Moringa oleifera Lam is often used in traditional medicine in several countries for the treatment of various illnesses. The plant was also found to contain bioactive compounds with therapeutic potential against various cancer cells. This study was carried out to determine the cancer cell inhibition of compounds from natural origins, specifically from the seeds of M. oleifera, where glucomoringin can be found abundantly and might carry the potential to inhibit the proliferation of prostate cancer cells. The crude seed extracts were obtained from water, acetone, chloroform, ethanol, methanol, and hexane. The water extract produced the highest crude yield (21.78%). The crude extracts were initially screened for phytochemical content, followed by cell viability tests using MTT assay against MCF 7, HepG2, DU 145, and PC-3 cell lines. Crude hexane, acetone and chloroform, were found to have coumarin and fat. Crude ethanol contains coumarin, quinone and fat. Crude methanol contains only saponin, coumarin and quinone, and finally, crude water contains saponin, alkaloid and coumarin. The crude water extract showed an inhibition (IC50) value with a time-dependent manner at 24, 48, and 72 hours of treatment. The crude water extract showed low IC50 against MCF 7 (39.95 μg/ml), Hep G2 (20.9 μg/ml), DU 145 (32.12 μg/ml), and PC-3 (4.12 μg/ml) at 72 hours respectively. The crude water extract was chosen to be use in the experiment because it was the most effective against the cell line that shows the lowest IC50 value as well as giving the highest crude yield All IC50 values are significant compared with control after analysis using one sample T-test (P <0.05) The crude water extract was used for further for compound isolation, which yielded 9.43% of glucomoringin (GMG). Subsequently, the compound was activated with myrosinase enzymes to yield its active compound, glucomoringin isothiocyanate (GMG-ITC), followed by characterization using high performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR) spectroscopy analyses. The isolated GMG-ITC was screened for its cytotoxicity, employing MTT assays against all the cell lines mentioned previously, and PC-3 was found to be more selective with IC50 of the isolated compound is 3.5 μg/ml. All IC50 values are significant compared to control after analysis using one sample T-test (P <0.05). The IC50 value of GMG-ITC was then used in the following studies, including morphological observation of apoptosis via AO/PI and TUNEL assays on the PC-3 cell line. The cell showed clear apoptotic body characterisation under phase contrast analysis, as well as colour changes with membrane blebbing and chromatin condensation in the AO/PI staining, followed by dark brown colour staining in the TUNEL assay due to nuclear DNA fragmentation of the cancer cells. The cytotoxic potency study was further performed with Annexin V-FITC, cell cycle analysis, mRNA quantification, and protein signalling. In Annexin V-FITC, the apoptosis cell activity increased significantly (P < 0.05) from 24, 48, to 72 hours of treatment compared to the control by GMG-ITC. The apoptotic cell percentage increased significantly (P<0.01) from 21.35% (24 hours), followed by 34.47% (48 hours) and finally 72.9% (72 hours) after treatment. The compound was observed to arrest the cell cycle at G2/M phase, which is an important phase in apoptosis. mRNA quantification indicates Nrf2 expression was downregulated significantly (P<0.05), but p53, Bax, and parp 6 were upregulated by the treatment of the GMG-ITC against PC-3 cell lines. The expression of p53 can be linked with a blockage of cell cycle progression at G2/M phase and the upregulation of Bax, caspase-3, while Bcl2 and Nrf2 were downregulated. Finally, protein analysis employing cell signalling immunoassay studies by Multiplex analysis revealed the modulation of apoptotic proteins after the treatment of the cancer cells with GMG-ITC. The expression of proteins in the analysis; JNK, Bad, Bcl2, and p53 were significantly upregulated (p<0.01) compared to control. It indicates that early apoptosis expression was triggered by the protein signalling induced by the treatment. In this study, apoptosis induction and DNA fragmentation processes were observed in treated PC-3 cells. These phenomena suggest that the bioactive compound from M. oleifera seed could be useful for future cytotoxic agent against prostate cancer.